A Delphi survey to determine a definition and description of hyperacusis by clinician consensus. (2nd August 2021) - Adams, Bethany; Sereda, Magdalena; Casey, Amanda; Byrom, Peter; Stockdale, David; Hoare, Derek J.
Abstract: Objective: There is currently no singularly accepted definition of hyperacusis. The aim of this study was to determine a definition and description of hyperacusis by clinician consensus. Design: A three-round Delphi survey involving hearing healthcare professionals built towards clinical consensus on a definition of hyperacusis. Round 1 involved three open-ended questions about hyperacusis. Seventy-nine statements were generated on descriptions, impact, sounds, and potential features of hyperacusis. Agreement on the relevance of each statement to defining or describing hyperacusis was then measured in Rounds 2 and 3. General consensus was defined a priori as ≥70% agreement, or ≥90 for clinical decision making. Study sample: Forty-five hearing healthcare professionals were recruited to take part in this study. Forty-one completed Round 1, 36 completed Round 2, and 33 completed Round 3. Results: Consensus was reached on 42/79 statements. From these a consensus definition includes "A reduced tolerance to sound(s) that are perceived as normal to the majority of the population or were perceived as normal to the person before their onset of hyperacusis". A consensus description of hyperacusis was also determined. Conclusions: This consensus definition of hyperacusis will help to determine the scope of clinical practice guidelines and influence needed research on hyperacusis.